PENERAPAN METODE CONSEPT MAP UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA KULIAH STATISTIKA I - Yunarti, Yuyun (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
Statististics instruction 1 is aimed at educating and training the students on how to collect, display, analysis, and interprete research data. Such skill is needed to writing final scientific paper.This research is also aimed at investigating the studentsâ motivativation and learning result in learning statistics by implementing concept map. This research was conducted in the fourth semester students of Islamic Education Department in academic year of 2013/2014 through two cycles. The firts cycle discussed data material, data display, and data analysis; while the second cycle discussed central tendency of data. Evaluation of each cycle is conducted through pre-test, post-test, discussion, and presentation. The result of this research shows that statistics instruction through concept map increased studentâ learning achievement in which the average score of pre-test of the first cycle is 35.13 while post-test is 80.69. Statistics instruction using map concept method increased studentsâ motivation with the percentage of 70.10. The students found that map concept helped increase their motivation and finally improve the result of statistics 1 instruction.Keywords: Concept map method, instruction, statistics